The retranslation of the sacre text: return or modernization? - G. T. Khukhuni; I. I. Valuitseva (Vestnik MGIMO-Universiteta, 2009)
The present article deals with the problem of the retranslation of the Bible in Christian tradition. The difference between Roman Catholic Church, Russian Orthodox Church and Protestant Churches is analyzed. Three main tendencies are postulated: 1) the return to the «right» text on sacred language and «purification» of the existing version; 2) striving for «modernization» – the transition from the traditional sacred language to the modern one; 3) the contamination of both tendencies, when the Bible is represented on «non-sacred» language, but the text is most archaized.